Operational Risk Management and Its Effect on Service Quality in Indonesian Logistics Companies - Febriyanti, Lia; Zhahira, Rafina Alya; Salsabila, Namira (Generasi Sains Indonesia, 2025)
The logistics sector in Indonesia faces complex operational challenges due to geographical conditions, infrastructure limitations, and increasing customer demands. These challenges create significant operational risks that may undermine service quality if not properly managed. This study aims to examine the effect of operational risk management (ORM) on service quality in Indonesian logistics companies. A quantitative explanatory research design was employed using survey questionnaires distributed to 120 logistics firms of different sizes across major cities. ORM practices including risk identification, assessment, contingency planning, monitoring, and technology adoption were measured alongside service quality dimensions based on the SERVQUAL model. Data were analyzed using descriptive statistics, correlation analysis, and multiple regression. The results indicate that all logistics firms face considerable risks, particularly transportation delays and infrastructure constraints. However, companies implementing structured ORM practices achieved higher service quality, especially in reliability and responsiveness. Correlation and regression analyses revealed that ORM significantly and positively influences service quality, with technology adoption emerging as the strongest predictor. In conclusion, ORM is not only a defensive measure but also a strategic enabler for enhancing service quality and competitiveness in the Indonesian logistics industry. Effective ORM ensures customer satisfaction, operational resilience, and sustainable business performance.